2023
DOI: 10.3390/su15021285
|View full text |Cite
|
Sign up to set email alerts
|

EntreComp Framework: A Bibliometric Review and Research Trends

Abstract: The European Entrepreneurship Competence (EntreComp) framework has been proposed by the European Commission in order to build consensus around a common understanding of entrepreneurship competence (knowledge, skills, and attitude). This study reports a bibliometric review of the research to date, addressing the EntreComp framework, based on documents published during the period from 2016 to June 2022. The research dataset was collected from Web of Science Core Collection (WoS) and included 37 articles. The bib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Thus, the existing research on entrepreneurial and sustainability competence frameworks has not considered GreenComp in comparison with EntreComp. Although there exists more research on EntreComp [39,40], GreenComp has received little attention so far [41]. Moreover, a thorough comparison of both is still missing.…”
Section: Literature Review Of Sustainability and Entrepreneurial Comp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the existing research on entrepreneurial and sustainability competence frameworks has not considered GreenComp in comparison with EntreComp. Although there exists more research on EntreComp [39,40], GreenComp has received little attention so far [41]. Moreover, a thorough comparison of both is still missing.…”
Section: Literature Review Of Sustainability and Entrepreneurial Comp...mentioning
confidence: 99%
“…A4 While there exists research on the EntreComp framework, for instance, Raţiu et al [39] or Joensuu-Salo et al [40], to date, no research has rigorously investigated EntreComp in conjunction with GreenComp. In their paper "EntreComp and GreenComp for Entrepreneurship.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The Entrepreneurial Culture Programs developed for years by the regional government of the autonomous region of Extremadura (called in Spanish Junta de Extremadura) are aligned with the European Entrepreneurial Competence Framework (EntreComp Europe), launched in 2016 by the European Commission [39]. Since then, several academic studies have focused attention on this framework [40][41][42]. Both the European framework and the entrepreneurship policy of the regional government of Extremadura, are based on the idea that the early development of entrepreneurial skills contributes to regional development, as previous studies on the topic have shown [43][44][45].…”
Section: The Big Picturementioning
confidence: 99%
“…Then, a presentation of the research questions, the methodology used, and the results of the research, is given. Using the Structural Equation Modeling (SEM) method, a statistical analysis of the five axes of the questionnaire used (based on the DigComp framework), is performed in order to unveil latent relationships concerning the research questions of this study [2].…”
Section: Introductionmentioning
confidence: 99%